Integration of RS/GIS and community knowledge-based data analysis for scenario modeling of water allocation management in downstream Angat River - Veneracion, Victor John J. (2009)
The Angat watershed in Bulacan supplies about 76% of the total domestic water needs of Metro Manila. The Angat dam also contributes about 200MW of hydroelectric power to the Luzon grid. But most people don't realize that the river also provide irrigation to almost 28, 000 hectares of farmlands in Central Luzon. It is also home to a wide variety of aquatic life and a source of livelihood for many living along the river. But since the construction of these dams and rapid urbanization, the Angat River suffered tremendous presseres which ultimately made it dry and polluted. Thus, an integrated water resource management IWRM approach is neede to remove the confussion and chaos caused by the different sector's disputes for water rights. The IWRM approach was formalized by the Technical Committee of the Global Water Partnership in year 2000, which aims to strike a balance between exploiting this finite resource for ensuring the livelihood of an increasing population and to protect and conserve the water resource.
The development of a decision support system is needed so that decision makers can assess the current status of the river and xplore alternatives ehich can maximize the allocation of water. The Water Evaluation and Planning WEAP software is such, a simulation based modeling tool operating on the basic principle of water balance accounting which allows analysis of furniture impacts based on changing hydrological events and institutional policies concerning water allocation. The complexities of doing hydrological modeling made it harder for modelers to acquire the needed water parameters and assess actual ground conditions. Thus, a method was developed to integrate remote sensing, GIS and knowledge based data with WEAP to provide the water parameters and also help facilitate model development.
The Angat River WEAP model provides a wide variety of scenarios affecting water allocation. Sample runs of the model revealed the importance of prioritizing the flow requirement of the downstream basin for ecological and livelihood purposes. The application of "water savings technology" for irrigation could help alleviate the watershortage. The study also explored the possibility of tapping groundwater as a secondary source of water for agricultural purposes. Combining all of the water saving measures and effective allocation, results would show that through efficient water management, savings of more than half of the irrigation requirements can be attained.
Overall, the RS-GIS-KB-WEAP model can address a lot of :what if" scenarios based on past, present, and future conditions that exist within the river system. However, the results of the simulation should be analyzed with due diligence on the assumptions and limitations of the model. With these limitations, this researcher managed to assess the impact of changing water priorities, government policies, and stakeholder behavior in a qualitative manner.
Thesis (M.S. Remote Sensing)--University of the Philippines, Diliman
Keywords: Water resources development -- Philippines; Watersheds -- Philippines -- Angat River; Water quality management -- Philippines -- Angat watershed